Creativity For Good Cards : Reshuffle Your Thinking - Creative Belgium; LUCA School of Arts (Berchem : Creative Belgium, 2023)
THE POWER OF CREATIVITY FOR GOOD : More than ever it is time to use creativity for good, to build brands that behave like responsible people. Creative Belgium encourages and recognizes the use of creativity to positively impact not only businesses and brands, but also the planet. That’s why Creative Belgium has partnered with LUCA School of Arts to create a card deck. The Creativity for good cards will help you to get to know the 17 Sustainable Development Goals and will reshuffle your thinking.
Keywords: Communicatie; Creativity; Gezelschapsspel; Kaartspel; Marketing